2014
DOI: 10.9734/bjmmr/2014/7518
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors and Spectacle Use Behavior among Medical Students in a Nigerian Medical School

Abstract: The study population consisted of fifth year medical students. Subjects had cycloplegic auto refraction with Topcon auto refractor during their rotation in ophthalmology at the Ophthalmology department of the University of Calabar Teaching Hospital. A spherical equivalents (SE) ≥ +0.50D were determined as hyperopia; SE of >-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
5
10
1
Order By: Relevance
“…Among medical students, the prevalence of refractive error was found to be 54% which is supported by the study conducted by Rajdeep et al 1 and Emmaneul Olu Megbelayin 3 et al in which it was 54% and 79.5% respectively. However, our study included a larger study group than the above studies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Among medical students, the prevalence of refractive error was found to be 54% which is supported by the study conducted by Rajdeep et al 1 and Emmaneul Olu Megbelayin 3 et al in which it was 54% and 79.5% respectively. However, our study included a larger study group than the above studies.…”
Section: Discussionsupporting
confidence: 52%
“…Poor vision in students has a negative influence on their future life as it affects productive performance in education thus in long term affecting the economic burden of the country. 3 Timely detection and intervention can tremendously improve student's potential during his or her formative years.…”
Section: Introductionmentioning
confidence: 99%
“…This results are comparable with studies done by Fledelius et al at Denmark, Chaudhry et al at Pakistan, Wu et al at China, Lv and Zhang at China Megbelayin et al at Nigeria, Gopalakrishnan et al at Malaysia, and Mavracanas et al at Greece reported that the prevalence of REs including myopia was higher among females as compared to their male counterparts. [11][12][13][14][15][16][17] On the contrary, a higher rate of myopia in males compared to females was observed at Baroda and Burdwan study though this was found to be of borderline significance and no significant difference between female and male students was observed in our study and Bangalore, Norway, Singapore, Hyderabad, and Turkey study. [18][19][20][21][22][23][24] It is possible that this slight variation in prevalence rates among medical students across different countries may be attributable to ethnic variations and different genetic predispositions.…”
Section: Discussionmentioning
confidence: 50%
“…The prevalence rate of myopia among those students were 63.6 percent. 7 In this study, the overall prevalence rate of hyperopia among medical students was 1.8 percent. A Norwegian study on 224 engineering students had reported a higher figure of hyperopia (30%).…”
Section: Discussionmentioning
confidence: 56%